Survival outcomes and epidemiology of Merkel cell carcinoma of the lower limb and hip: A Surveillance, Epidemiology, and End Results analysis 2000-2018Capsule Summary - Matteo Scampa, MS; Rastine Merat, MD, PhD; Evangelia Tzika, MD; Daniel F. Kalbermatten, MD, PhD; Carlo M. Oranges, MD, PhD (JAAD International, 2022)
Background: Merkel cell carcinoma of lower limb and hip skin is a rare skin tumor that has a high recurrence rate. Objective: To assess epidemiology and survival outcomes of the lower limb and hip Merkel cell carcinoma, which are less addressed in the literature. Methods: The Surveillance, Epidemiology, and End Results database was searched for all cases of skin Merkel cell carcinoma between 2000 and 2018. Demographic and clinicopathologic features were compared between lower limb and other skin localizations using the t test or χ2 test. The overall survival (OS) of lower limb Merkel cell carcinoma was calculated using the Kaplan-Meier method. Subgroups were compared using the log rank test. Multivariate cox regression was used to identify independent prognostic factors. Results: In total, 976 patients were identified. The mean age was 72.7 years. The median OS was 68 months, better than that of other localizations. Older age, regional lymph node, and distant metastasis were associated with low OS. Surgery with >1-cm margins, when associated with radiotherapy, had the best OS. Age, tumor size, lymph node status, presence of metastasis, and treatment sequence were identified as independent prognostic factors. Conclusion: Lower limb and hip Merkel cell carcinomas have better OS than tumors in other skin localizations. In this dataset, the best OS was ensured using surgery with >1-cm margins and adjuvant radiotherapy.